2019
DOI: 10.1007/s40430-019-1776-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the thermal mixing enhancement in a T-junction pipe

Abstract: In this paper, three-dimensional numerical simulations are conducted to study the thermal mixing of turbulent flow in a T-junction with hot fluid flowing in the main pipe and cold fluid in the branch. The main objective is to investigate the effects of the axial and cross-injection angles to the main pipe and the branch-to-main flow rate ratio on the turbulent thermal mixing. In this regard, an appropriate mixing index is proposed to evaluate the thermal mixing efficiency. The turbulence model employed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The thermal mixing performance of hot and cold fluids can be defined by Temperature Mixing Degree (TMD). This TMD can be expressed as [35],…”
Section: Thermal Mixing Performancementioning
confidence: 99%
“…The thermal mixing performance of hot and cold fluids can be defined by Temperature Mixing Degree (TMD). This TMD can be expressed as [35],…”
Section: Thermal Mixing Performancementioning
confidence: 99%
“…To find out thermal mixing performance of hot and cold fluids more accurately, it is required to calculate the Temperature Mixing Degree, TMD [32], defined as:…”
Section: Calculation Of Thermal Mixing Efficiencymentioning
confidence: 99%
“…Results showed that a 90 • bend had a strong effect on the fluid mixing mechanism and the momentum ratio between the main velocity and the branch velocity of the T-junction, which could be an important parameter for the classification of the fluid mixing mechanism. The thermal mixing of turbulent flow in a T-junction with hot fluid flowing in the main pipe and cold fluid in the branch by three-dimensional numerical simulations was investigated by Hekmat et al [15]. They concluded that the injection angles and flow rate ratios had significant influence on the reverse and secondary flow on the mixing.…”
Section: Introductionmentioning
confidence: 99%